Antifungal polysulphides from Petiveria alliacea L. - Benevides, PJC; Young, MCM; Giesbrecht, A. M.; Roque, N. F.; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 2001)
Bioactivity-directed fractionation of the CH2Cl2/MeOH (2:1, v/v) extract of the roots of Petiveria alliacea, using mutant yeast strains of Saccharomyces cerevisiae and fungi Cladosporium cladosporioides and C. sphaerospermum led to the isolation of dipropyl disulphide (1), dibenzyl sulphide (2), dibenzyl disulphide (3), dibenzyl trisulphide (4), dibenzyl tetrasulphide (5), benzylhydroxymethyl sulphide (6) and di(benzyltrithio) methane (7). of these, 5-7 are new compounds and this is the first report of the natural occurrence of 2 and 3. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: Petiveria alliacea; Phytolacaceae; antifungal polysulphides